The Effectiveness of Peer Tutoring in Overcoming Early Reading Difficulties at Ibnu Sina Elementary School in Bandung - Budi Hermawan; Aksan Romadlon; Andayani Ratnawati; Asep Dahliyana (Jurnal ORTOPEDAGOGIA, 2025)
This study aims to assess the effectiveness of peer tutoring in enhancing early reading skills among second-grade students with reading difficulties at Ibnu Sina Islamic Elementary School, Bandung. Employing a Classroom Action Research (CAR) design, adapted from Kemmis & McTaggart, and conducted in two cycles, this investigation used a mixed-method approach to ensure a comprehensive picture regarding the intervention's impact on early literacy competencies and the social dynamics of learning. Data collection was made through a pre-test-post-test, structured observation, and reflective interviews. Statistical analysis showed that the average rise in reading scores reached 55%, and the results of the paired t-test indicated that this increase was significant (p < 0.05). Qualitative data show that the increasing engagement, self-confidence, and quality of the interaction between tutors and tutees are in tune with the latest literature, which highlights that peer tutoring is an effective practice to enhance academic achievement, self-regulation, and social-emotional support within elementary education settings. This study concludes that peer tutoring can serve as a low-cost and highly relevant instructional strategy for addressing early reading difficulties in elementary school settings, and it recommends strengthening tutor training and improving the quality of teacher scaffolding for program sustainability.